Patient experience of telehealth for the self-management of chronic disease: applying a value co-creation framework - Go Jefferies, Josephine Kian Wie (2017)
This thesis is a study of patient experience of telehealth services for self-management of chronic disease. It investigates the use of technology-based services to address the social and managerial problem of unsustainable demand for scarce resources by focusing on the understudied patient perspective. Chronic disease care is a ‘wicked problem’ affected by complex interdependencies that are difficult to change, such as rising demand from ageing populations, unhealthy lifestyles, spiralling healthcare costs and economic contraction weakening the financial foundations of healthcare systems. Studies suggest that using technology-based services installed in patient homes can play a part in safely reducing demand for in-clinic appointments and emergency hospitalisations.